Pharmacokinetic Prediction, Drug-Like Properties, and Molecular Docking of Bioactive Compounds from Ethanol Extract of Uncaria nervosa Elmer Leaves - Rahmawati, Noveri; Herli, Muhammad Azhari; Delvi Andrianingsih; Rahmi Amini (The Journal Of Pharmacy, 2025)
Uncaria nervosa Elmer leaves are known to contain bioactive compounds with potential as natural drug candidates, yet their pharmacokinetic profiles, drug-likeness, and molecular affinity toward target proteins remain limitedly explored. This study aimed to evaluate the pharmacokinetic properties, drug-likeness, and molecular interaction potential of bioactive compounds from the ethanol extract of Uncaria nervosa leaves. An in silico approach was employed using SwissADME to analyze pharmacokinetic parameters (absorption, distribution metabolism, and excretion) and drug-likeness based on Lipinski’s and Veber’s rules, followed by molecular docking against proteins 6O0K and 2W3L using MOE software. The results showed that most compounds exhibited high gastrointestinal absorption, did not inhibit major CYP enzymes, and several complied with drug-likeness rules. Docking analysis revealed that ceratodictyol displayed the closest binding energy to the positive controls (doxorubicin and obatoclax), indicating strong molecular affinity, while N-formamide showed superior pharmacokinetic and drug-likeness properties. In conclusion, the combination of pharmacokinetic and docking data highlights ceratodictyol as the main candidate supported by N-formamide as a potential compound, suggesting that Uncaria nervosa leaf extract may serve as a promising natural source for anticancer drug development.